Live-cell microarray surface coatings supporting reverse transduction by adeno-associated viruses. (October 2011) - McConnell, Kellie I.; Schweller, Ryan M.; Diehl, Michael R.; Suh, Junghae
High-throughput live-cell microarray technologies that facilitate combinatorial screening of genes and RNA interference (RNAi) would be invaluable in the identification of key gene expression profiles involved in complex cellular behaviors. Each spot on such a microarray can comprise a unique combination of genes or RNAi packaged into gene delivery vectors. Live target cells seeded on top of the microarrays would express the combination of genetic factors, potentially leading to phenotypic changes within cells. Here, we investigate the feasibility of using adeno-associated virus (AAV) as a gene delivery agent for such live-cell genetic microarrays. A robotic spotter was used to deposit AAV onto gamma-amino propyl silane, amine silane, or nitrocellulose-coated glass slides. Virus deposition and reverse transduction of target cells were found to be surface coating–dependent with nitrocellulose coating yielding the best AAV deposition, while also producing discrete islands of highly transduced cells. Our results demonstrate the feasibility of using nitrocellulose-coated surfaces for the development of AAV-based genetic microarrays.